The Development of a Web-Based, Patient-Centered Intervention for Patients With Chronic Myeloid Leukemia (CMyLife): Design Thinking Development Approach - Ector, Geneviève ICG; Westerweel, Peter E; Hermens, Rosella PMG; Braspenning, Karin AE; Heeren, Barend CM; Vinck, Oscar MF; de Jong, Jan JM; Janssen, Jeroen JWM; Blijlevens, Nicole MA (JMIR Publications, 2020)
BackgroundWith the global rise in chronic health conditions, health care is transforming, and patient empowerment is being emphasized to improve treatment outcomes and reduce health care costs. Patient-centered innovations are needed. We focused on patients with chronic myeloid leukemia (CML), a chronic disease with a generally good long-term prognosis because of the advent of tyrosine kinase inhibitors. However, both medication adherence by patients and guideline adherence by physicians are suboptimal, unnecessarily jeopardizing treatment outcomes. ObjectiveThe aim of this study was to develop a patient-centered innovation for patients with CML using a design thinking methodology. MethodsThe 5 phases of design thinking (ie, empathize, define, ideate, prototype, and test) were completed, and each phase started with the patient. Stakeholders and end users were identified and interviewed, and observations in the care system were made. Using tools in human-centered design, problems were defined and various prototypes of solutions were generated. These were evaluated by patients and stakeholders and then further refined. ResultsThe patients desired (1) insights into their own disease; (2) insights into the symptoms experienced, both in terms of knowledge and comprehension; and (3) improvements in the organization of care delivery. A web-based platform, CMyLife, was developed and pilot-tested. It has multiple features, all targeting parts of the bigger solution, including a website with reliable information and a forum, a guideline app, personal medical records with logs of symptoms and laboratory results (including a molecular marker and linked to the guideline app), tailored feedback based on the patients' symptoms and/or results, screen-to-screen consulting, delivery of medication, and the collection of blood samples at home. ConclusionsThe multifeatured innovation, CMyLife, was developed in a multidisciplinary way and with active patient participation. The aim of developing CMyLife was to give patients the tools to monitor their results, interpret these results, and act on them. With this tool, they are provided with the know-how to consider their results in relation to their personal care process. Whether CMyLife achieves its goal and the evaluation of the added value will be the focus of future studies. CML could become the first malignancy for which patients are able to monitor and manage their disease by themselves.